Meta-analysis of the diagnostic value of 18F-FDG PET/CT in the recurrence of epithelial ovarian cancer - Wang, Xiaoyan; Yang, Lifeng; Wang, Yan (Frontiers in Oncology, 2022)
Background Ovarian cancer is the leading cause of cancer-related death among gynecologic malignancies. With much evidence suggesting that 18F-FDG PET/CT may be an excellent imaging test for the diagnosis of epithelial ovarian cancer recurrence, we conducted a systematic review and meta-analysis to summarize relevant studies and evaluate the accuracy and application value of 18F-FDG PET/CT in the diagnosis of recurrence of epithelial ovarian cancer. Materials and methods Clinical trials of 18F-FDG PET/CT for the diagnosis of recurrence of epithelial ovarian cancer were systematically searched in PubMed, Embase, Cochrane Library, Web of Science and OVID database. The relevant literature was searched until May 22, 2022. Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) was used to evaluate the quality of the included original studies, and the meta-analysis was performed using a bivariate mixed-effects model and completed in Stata 15.0. Results A total of 17 studies on 18F-FDG PET/CT for the diagnosis of epithelial ovarian cancer recurrence were included in this systematic review, involving 639 patients with epithelial ovarian cancer. Meta-analysis showed that the sensitivity, specificity and area under the curve of 18F-FDG PET/CT for the diagnosis of epithelial ovarian cancer recurrence were 0.88 (95% CI: 0.79 - 0.93), 0.89 (95% CI: 0.72 - 0.96) and 0.94 (95% CI: 0.91- 0.96), respectively. Subgroup analysis showed higher diagnostic efficacy in prospective studies than in retrospective studies, and no significant publication bias was observed in Deeks’ funnel plot, with sensitivity analysis revealing the stability of results. Meta regression shows that the heterogeneity of this study comes from study type. Conclusion 18F-FDG PET/CT has good diagnostic value in the recurrence of epithelial ovarian cancer.